The Influence of Political Awareness on the Electoral Participation of Voters with Disabilities in Indonesia - Yudha Alam, Wira; Anastasia Puspa Anggraini, Anastasia; Dwijayanti, Ririn; Zulvamita Anggraini, Rika (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
The participation of voters with disabilities in elections is one of the important aspects in realizing an inclusive democracy. This study aims to investigate the influence of political awareness on the level of participation of voters with disabilities in elections in Indonesia. Using qualitative methods and literature study techniques, this study analyzes various relevant sources, including scientific articles, policy reports, and previous studies. The results of the analysis show that high political awareness contributes significantly to the participation of voters with disabilities. Voters who are aware of their political rights tend to be more active in exercising their right to vote, even though they are still faced with various challenges such as physical accessibility and limited information. Therefore, this study recommends the need for greater efforts to increase political awareness through inclusive education and the provision of disability-friendly information. The results of this study are expected to contribute to the development of more inclusive election policies in Indonesia.